Oral Iloprost Improves Endobronchial Dysplasia in Former Smokers - Keith, Robert L. (2011)
There are no established chemopreventive agents for lung cancer, the leading cause of cancer death in the United States. Prostacyclin levels are low in lung cancer and supplementation prevents lung cancer in preclinical models. We carried out a multicenter double-blind, randomized, phase II placebo-controlled trial of oral iloprost in current or former smokers with sputum cytologic atypia or endobronchial dysplasia. Bronchoscopy was performed at study entry and after completion of six months of therapy. Within each subject, the results were calculated by using the average score of all biopsies (Avg), the worst biopsy score (Max), and the dysplasia index (DI). Change in Avg was the primary end point, evaluated in all subjects, as well as in current and former smokers. The accrual goal of 152 subjects was reached and 125 completed both bronchoscopies (60/75 iloprost, 65/77 placebo). Treatment groups were well matched for age, tobacco exposure, and baseline histology. Baseline histology was significantly worse for current smokers (Avg 3.0) than former smokers (Avg 2.1). When compared with placebo, former smokers receiving oral iloprost exhibited a significantly greater improvement in Avg (0.41 units better, P = 0.010), in Max (1.10 units better, P = 0.002), and in DI (12.45%, P = 0.006). No histologic improvement occurred in current smokers. Oral iloprost significantly improves endobronchial histology in former smokers and deserves further study to determine if it can prevent the development of lung cancer.